Outcome of mammography in women with large breasts - Gayde, C.; Goolam, I.; Bangash, H.; Tresham, J.; Fritschi, Lin; Wylie, E. (Springer, 2012)
Mammography has been established as an effective screening tool for the early detection of breast cancer. Obesity may lead to increased breast size and has been linked to increased rates of breast cancer. As women with larger breasts may be predisposed to developing cancer, it is important that mammography is an appropriate test in these women. This study investigated the sensitivity and specificity of mammography in women with larger breasts in a population screening program. Method: Data was obtained from 848 648 eligible screening episodes of women aged over 40. Of these episodes, 758 860 were eligible for the study, with 7.2% (54 879 screens) deemed to have large breasts. Large breasts were defined as those for whom at least one large cassette was used in the mammographic process. Those women having only four standard cassettes per screen were classified as having average size breasts (703 981 screens, 92.8%). Cancer detection rates, interval cancer rates (false negatives) and recall to assessment rates were compared for women examined on standard sized cassettes versus large cassettes. Chance corrected measures of sensitivity and specificity and 95% confidence intervals (CI) were calculated for women with and without large breasts. Results: The study found that the sensitivity and specificity of mammography was greater for larger breasted woman. The incidence of breast cancer was also found to be higher in woman with larger breasts in the combined population (73.1 per 100,000 (95% CI 65.9–80.2) in large breasted women versus 52.8 (95% CI 51.1–54.5) in other women) and in each of the specific age groups. This study confirms the appropriateness of mammographic screening for women with large breasts.